PERCEPTION OF TRAUMATIC CHILDBIRTH OF WOMEN AND FACTORS AFFECTING - Koc, Ozlem; Ozkan, Hava (Dokuz Eylul Univ Inst Health Sciences, 2022)
Backround: Mothers' perceptions of labor, their perspectives on the birth process and the events they experience in this process, and the meanings they attribute to them may differ. Aim: This study was conducted to determine women's perception of traumatic birth and the affecting factors. Design and Methods: The data of the study were collected online between February 1 and April 10, 2021. A nonrandom sampling method, the snowball sampling method, was used in the study. Data were collected using The Trauma Perception Scale for Regarding Birth. (TPSRP) The mean, percentage, variance, and Cronbach's a were calculated. Findings: The mean TPSRB score was calculated as 120.70 +/- 14.63. According to the mean score, it was determined that the mothers' perceptions of traumatic birth were high. The difference between the TPSRB scores according to age, education level, employment status, social security, income level, family structure, duration of marriage, number of births, number of children and receiving prenatal care is found statistically significant. (p<0.05). Conclusion: Midwives and nursings have important duties in order to improve the perception of traumatic birth, which affects women so much, and to leave its place to positive birth experiences.
Keywords: Childbirth; Postpartum care; Post traumatic stress disorder; Risk factors